Study on the effect of etching process of NMOS structure using Silvaco TCAD tools: article - Abd Rahim, Mohd Shahrir; Mohd Noor, Uzer (2008)
The effect due to the etching process of NMOS structure using Silvaco TCAD tools software was investigated using different etching methods by varying the etch rate and divergence rate. The etching methods are isotropic wet etching method and isotropic RIE etching method where the length of polysilicon gate and threshold voltage were decreased by increasing the etch rate. The chemical RIE etching method provided highly selectivity and directionality gives various divergence rates. The directional RIE etching method gave similarities in term of etch profile, junction depth and threshold voltage characteristic compared to the reference geometrical etching method for any etch rate and divergence rate.